How I grew - McCarthy, Mary 1912-1989 (Harcourt Brace Jovanovich, 1987)
The award-winning author offers a memoir of her adolescence, with revelations of family, neighbors, classmates and teachers, critical comments on reading, comparative views of places, and observations of various events.
Keywords: McCarthy, Mary <1912-1989> -- Childhood and youth; McCarthy, Mary -- 1912-1989; Geschichte 1900-2000; Authors, American -- 20th century -- Biography; Autobiografie -- 1925-1933